Treatment outcomes of visceral leishmaniasis in Ethiopia from 2001 to 2017: a systematic review and meta-analysis - Eyob Alemayehu Gebreyohannes; Akshaya Srikanth Bhagvathula; Tadesse Melaku Abegaz; Mohammed Assen Seid (BMC, 2018)
Abstract Background Ethiopia has the highest number of visceral leishmaniasis (VL) cases after Sudan in Sub-Saharan Africa. However, there was lack of comprehensive data on VL treatment outcome despite the huge burden of the diseases in the country. Hence, we aimed to perform a systematic review and meta-analysis on this topic to obtain stronger evidence on treatment outcomes of VL from the existing literature in Ethiopia. Methods The Cochrane guidelines to conduct meta-analysis following the Preferred Reporting Items for Systematic review and Meta-Analysis statement was used to conduct a computerized systematic search of the PubMed, Google Scholar, and ScienceDirect databases. Random effects model was used to combine studies showing heterogeneity of Cochrane Q P < 0.10 and I 2  > 50. Treatment outcomes were assessed at end of treatment and at 6 months follow-up. Subgroup analyses were performed on treatment outcomes based on the different antileishmanial treatment options and patients' HIV status. Results Fifteen studies were included in the final analyses. At end of treatment, an overall treatment success rate of 82.6% was noticed. At 6 months follow-up, the overall treatment success rate was 72.2%. For patients treated with sodium stibogluconate (SSG), the treatment success rates at the end of treatment and at six-month follow-up were 81.5% and 80.7%, respectively. Multiple doses of liposomal-amphotericin B (L-AMB) had treatment success rates of 96.7 and 71-100% at the end of treatment and at 6 months follow-up, respectively. The combination of SSG with paromomycin (PM) gave treatment success rates of up to 90.1% at the end of treatment. HIV-infected individuals were found to have a higher mortality (odds ratio = 4.77, 95% CI: 1.30-17.43, P = 0.009) rate at 6 months follow-up. Conclusions SSG alone has shown lower treatment efficacy in the management of VL when compared to combination of SSG with PM and multiple doses of L-AMB. The combination of SSG with PM gave good treatment success rates with shorter duration of treatment. Hence, the combination of SSG with PM should be used preferentially over SSG monotherapy. Multiple doses of L-AMB showed great efficacy especially among patients with complications, severe disease, HIV co-infection, and intolerance to the adverse effects of antimonials. HIV-infected individuals had a worse prognosis than their HIV-negative counterparts.